Laser Therapy Versus Electromagnetic Field on Mucosal Membrane Thickening in Children with Chronic Rhinosinusitis - Abdulrashid, Nessrein Afify; Ayoub, Hamada El-Sayed; Abdelkader, Ahmed Mamdouh (Journal of Lasers in Medical Sciences, 2019)
Introduction: Rhinosinusitis is a frequent disease in children but may be underdiagnosed, that is to say, several causes of the disease are missed in children. Therefore, it seems essential to provide other modalities to treat chronic health conditions like such cases. This controlled clinical study was conducted to compare the effect of two non-pharmacological, painless, safe modalities; low-level laser therapy (LLLT), with pulsed electromagnetic field (PEMF) on mucosal membrane thickening in children with chronic rhinosinusitis. Methods: Thirty children with chronic sinusitis participated in this study, their ages ranged from 6 to 13 years old, recruited from the outpatients ENT clinic, Kasr Al Aini teaching hospital. They were classified into 2 groups of equal number; study group A (PEMF group) and study group B (LLLT group). These children were evaluated before the starting and after the end of the study through CT scan full examination (coronal and axial) for all children. Results: This study showed that there were statistically significant improvements in mucosal membrane thickness in both groups (P < 0.05), while there was no statistically significant difference between groups (P > 0.05). Conclusion: From the obtained outcomes it can be concluded that both the laser and electromagnetic field can be used effectively in the management of symptoms in children with chronic rhinosinusitis, while no significant difference between these modalities obtained.